2021
DOI: 10.1080/13467581.2021.1908899
|View full text |Cite
|
Sign up to set email alerts
|

Construction workers’ awareness of safety information depending on physical and mental load

Abstract: Construction is one of the most dangerous occupations. The most prominent reason for worker accidents is unsafe behavior, particularly rooted in the inability to recognize and appropriately respond to risk factors. Previous studies have investigated worker perception and comprehension of construction hazards and safety information in laboratory settings. A relationship has been found between workload and workers' situation awareness (SA), a useful concept for understanding risk perception and comprehension. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Task complexity, for example, has been associated with reduced performance and SA and increased mental workload (Fang et al 2018), which may require specific training scenarios to mitigate the reduction of the operator's SA levels during more complex tasks (Choi et al 2020). Finally, for similar levels of task complexity, construction workers' SA is significantly affected by different levels of MWL, with SA decreasing for higher levels of MWL (Kim et al 2021).…”
Section: Situational Awarenessmentioning
confidence: 99%
“…Task complexity, for example, has been associated with reduced performance and SA and increased mental workload (Fang et al 2018), which may require specific training scenarios to mitigate the reduction of the operator's SA levels during more complex tasks (Choi et al 2020). Finally, for similar levels of task complexity, construction workers' SA is significantly affected by different levels of MWL, with SA decreasing for higher levels of MWL (Kim et al 2021).…”
Section: Situational Awarenessmentioning
confidence: 99%
“…On the other hand, concerns such as tight project budget and time constraints lead construction personnel to be production-oriented, which puts field employees under mental pressure (Mitropoulos et al, 2005). Moreover, workers face mental fatigue and stress due to poor working conditions, which cause unsafe acts (Jebelli et al, 2019;Kim et al, 2022). Furthermore, improving the physical conditions of workers is an effective means of promoting safe behavior.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Furnham [25] developed an accident causal process model showing that incomplete cognition of hazards can cause multiple human errors. Previous research revealed that keeping good SA is even harder for people who work in a dynamic and less organized environment, such as military, construction, and road environments [26][27][28]. Salmon et al [29] identified some implications of the theory of SA regarding the use of road environments and explained accident causation based on the theory.…”
Section: Construction Worker Hazard Recognition and Risk Perceptionmentioning
confidence: 99%